2016
DOI: 10.18632/oncotarget.12480
|View full text |Cite
|
Sign up to set email alerts
|

A functional signal profiling test for identifying a subset of HER2-negative breast cancers with abnormally amplified HER2 signaling activity

Abstract: The results of clinical trials evaluating the efficacy of HER2 inhibitors in patients with breast cancer indicate that the correlation between HER2 receptor levels and patient outcomes is as low as 50%. The relatively weak correlation between HER2 status and response to HER2-targeting drugs suggests that measurement of HER2 signaling activity, rather than absolute HER2 levels, may more accurately diagnose HER2-driven breast cancer. A new diagnostic test, the CELx HER2 Signaling Profile (CELx HSP) test, is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…Previous analysis of 34 HER2-negative breast tumor cell samples using the CELx HSF test indicated that 20.5% (95% CI 10.0-37.1) of these samples were HER2-/ HSFs+ (Huang et al 2016(Huang et al , 2017. Further work screening multiple HER2+ and HER2− cell lines and patient samples demonstrated that there was no significant correlation between HER2 receptor expression level and the HER2-initiated signaling activity quantified by the CELx HSF Test (Huang et al 2017).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous analysis of 34 HER2-negative breast tumor cell samples using the CELx HSF test indicated that 20.5% (95% CI 10.0-37.1) of these samples were HER2-/ HSFs+ (Huang et al 2016(Huang et al , 2017. Further work screening multiple HER2+ and HER2− cell lines and patient samples demonstrated that there was no significant correlation between HER2 receptor expression level and the HER2-initiated signaling activity quantified by the CELx HSF Test (Huang et al 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Methods for sample collection, storage, transport, tissue extraction, and primary cell culture have been previously described (Huang et al 2016(Huang et al , 2017. Briefly, patient breast tumor tissue was delivered from the participating clinic to the laboratory in less than 30 h at 0-8 °C, accessioned, and then minced with scalpels to < 2-mm pieces and either used fresh or cryopreserved until further analysis (Unisol, Cell and Tissue Systems, Charleston, SC).…”
Section: Establishment Of Primary Breast Tumor Cell Culturesmentioning
confidence: 99%
See 3 more Smart Citations